2013
DOI: 10.1007/s13187-013-0509-6
|View full text |Cite
|
Sign up to set email alerts
|

Tangled in the Breast Cancer Web: an Evaluation of the Usage of Web-Based Information Resources by Breast Cancer Patients

Abstract: This study describes Internet use by breast cancer patients highlighting search patterns and examining the impact of web-based information on the clinical encounter. From September 2011 to January 2012, breast cancer patients at a cancer center completed a survey. Answers were closed and open-ended. Eighty-one patients were approached and 56 completed the survey. Forty-five (80 %) respondents used the Internet and 32 (71 %) searched for breast cancer information. All used Google as their principal search engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 31 publications
6
56
1
2
Order By: Relevance
“…Likewise, over half found it impacted their clinical encounter with their melanoma specialist which was again comparable to our breast cancer study [13]. This is echoed to some extent in other studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Likewise, over half found it impacted their clinical encounter with their melanoma specialist which was again comparable to our breast cancer study [13]. This is echoed to some extent in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…A large percentage of Internet users in our study identified that the Internet influenced their treatment decision, similar to our breast cancer study [13]. Likewise, over half found it impacted their clinical encounter with their melanoma specialist which was again comparable to our breast cancer study [13].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Paralelamente, si atendemos al uso que hacen de internet los pacientes oncológicos, los estudios indican que un 70-97% de ellos buscan información médica online (23,24 ). Este uso de internet se incrementa significativamente después del diagnóstico y se mantiene en la fase de supervivencia extendida, lo que indicaría necesidades de información no cubiertas (25) .…”
Section: Introductionunclassified